INSTRUMENTAL TRANSCOMMUNICATION IN DIGITAL NETWORKS: HYBRID DEVICES ON THE BORDERLINE OF SCIENCE AND SPIRITUALITY - Melo, José Valentim Martins; Costa, Edwaldo (Seven Editora, 2026)
This article examines Instrumental Transcommunication (ITC) as a hybrid communicational phenomenon in contemporary Brazilian digital culture. Through qualitative methodological triangulation, we analyze how ITC, mediated by electronic devices and Generative Artificial Intelligence (GAI), reconfigures discourses on grief, religious authority, and scientific legitimacy on digital platforms. The results reveal ITC as a symptom of technoculture, where belief and skepticism dispute regimes of truth through amateur scientification practices. We argue that this emerging field challenges paradigms of public science communication, demanding new epistemological approaches.